2017
DOI: 10.5536/kjps.2017.44.4.225
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Health Management System on the Growth of Chicken Small Farm in Southwest States of Nigeria

Abstract: Chicken production remains the foremost endeavor in the Nigerian livestock industry. However, disease incidence has been a major constraint on the growth of this subsector. This study assessed health management practices and disease incidence in smallholder chicken production enterprise in Southwest Nigeria using data from a farm survey of 240 farmers selected using a multistage sampling technique from 5 of 6 states in Southwest Nigeria. The study showed that vaccination was given by 96.8% of the famers, 97.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The decrease in mortality and the increase in average egg per bird between 2017 and 2018 points to improvement in the managerial capabilities of the farmers. Saka et al (2017) also reported a mortality rate of 37.8% for poultry farmers in Southwest Nigeria. The high mortality rate in 2017 translates to loss of investment and earning potentials among farmers.…”
Section: Productivity Of Chicken Egg Farmersmentioning
confidence: 96%
See 1 more Smart Citation
“…The decrease in mortality and the increase in average egg per bird between 2017 and 2018 points to improvement in the managerial capabilities of the farmers. Saka et al (2017) also reported a mortality rate of 37.8% for poultry farmers in Southwest Nigeria. The high mortality rate in 2017 translates to loss of investment and earning potentials among farmers.…”
Section: Productivity Of Chicken Egg Farmersmentioning
confidence: 96%
“…They are characterized by shortage of capital cum low level of investment and its attendant low level of adoption of productivity enhancing technologies and production practices. Other constraints include high feed cost, high mortality and poor access to market among others (Apantaku, 2006;Akanni, 2007;Olaniyi et al, 2008;Adeyemo and Onikoyi, 2012;Adesehinwa et al, 2016;Saka et al, 2017). Most of these challenges are traceable to deficiencies of farmers as regards appropriate management and entrepreneurial skills, dwindling capacities to access or procure required inputs or adopt recommended routine h y g i e n e o r b i o -s a f e t y m e a s u r e s .…”
Section: Introductionmentioning
confidence: 99%